THE ROLE OF LOCAL GOVERNMENTS IN THE DECISIONS OF THE CONFERENCE OF THE PARTIES (COP): CONTRIBUTIONS AND POLICY TRENDS IN CLIMATE ACTION (Third Sector Social Economic Review, 2025)
This study aims to analyse the role, contributions and policy trends of local governments in the decisions of the Conferences of the Parties (COP) held under the United Nations Framework Convention on Climate Change (UNFCCC). In the study, a total of 66 decision documents of all conferences from COP1 to COP26 were analysed and the reflections of concepts such as ‘local governments’, ‘city’ and ‘urban’ in the context of climate change were analysed. The conferences from COP26 to COP29 were evaluated in the light of the information on the official website of UNFCCC. In this context, by analysing the decision texts of different COP meetings, it is aimed to analyse the extent to which the themes related to local governments and cities are addressed in which conferences and how they have changed over time; to reveal the emphasis on the role of local governments and cities in climate action in these conferences, to analyse the change in these roles and their effects on policy processes. The findings obtained detail the increasing importance of local governments in the fight against climate change and their visibility in the COP processes and the themes in which the policies related to local governments are concentrated in the COP processes and how these themes are reflected in the decision texts. In particular, the impact of turning points such as the 2015 Paris Agreement on the role of local governments is emphasised. As a result, the study aims to reveal the importance of local governments in the fight against climate change, to evaluate the applicability of COP decisions at the local level and to provide recommendations for future processes. In this context, the research findings are a road map for increasing the contribution of local governments in climate action.
Keywords: Local governments; Conferences of Parties (COP); Climate action; Sustainable Development; Climate change.